The Caesar Affair - Brand, Aaron (My University, 2014)
In late 1916, the Armenian and Syrian Relief Committee arranged for supplies to be delivered by the U.S. Naval Collier USS Caesar to the Red Cross in Beirut to relieve famine in Mount Lebanon. Political obstruction diverted the ship. The failure was the final effort by the Red Cross in Syria during the war.
1914-1918-online. International Encyclopedia of the First World War
PUBLISHED
Keywords: USS Caeser; Syria; Red Cross; Armenian Syrian Relief Committee; First World War; WWI; Armenia; First World War; First World War and its legacy; The Red Cross; World War 1